KAJIAN EXPERIMENTAL KUAT TARIK REBAR DENGAN VARIASI KEDALAMAN DAN DIAMETER - Parada Afkiki Eko Saputra; Benaya Surya Ginting (Universitas Quality, 2021)
The failure of the structure of reinforced concrete beams in buildings can be caused by various factors including design errors, implementation, and changes in building functions. To overcome structural failure, structural reinforcement can be used using adhesives as reinforcing material in the planting of new reinforcement with a certain depth. To find out the strength of the adhesive and the strength of tensile reinforcement, a study was carried out on the specimen using variations in the diameter and depth. The rebar diameter used in this study was T10 and T13 with variations in T10 depths of 6, 10, and 12cm while those for rebar T13 were 7, 11, and 13cm. Based on the results of testing the tensile strength of rebar T10 at a depth of 6 cm resulted in a tensile strength of 40 kN, at a depth of 10 cm resulting in a tensile strength of 50 kN, at a depth of 12 cm resulting in a tensile strength of 55 kN. While the tensile strength test of rebar T13 at a depth of 7 cm resulted in a tensile strength of 35 kN, at a depth of 11 cm yielding a tensile strength value of 20 kN at a depth of 13 cm resulting in a strong value pull at 55 kN. Based on the results of the study it can be concluded that depth affects the value of tensile strength of rebar.